2015
DOI: 10.5194/bg-12-653-2015
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends and drivers of regional sources and sinks of carbon dioxide

Abstract: The land and ocean absorb on average over half of the anthropogenic emissions of carbon dioxide (CO2) every year. These CO2 “sinks” are modulated by climate change and variability. Here we use a suite of nine Dynamic Global Vegetation Models (DGVMs) 5 and four Ocean Biogeochemical General Circulation Models (OBGCMs) to quantify the global and regional climate and atmospheric CO2 – driven trends in land and oceanic CO2 exchanges with the atmosphere over the period 1990–2009, attribute these trends to underlying… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
830
2
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 750 publications
(859 citation statements)
references
References 170 publications
24
830
2
3
Order By: Relevance
“…It was estimated, by fitting a harmonic model to monthly-mean ACTE, seasonal amplitude of ACTE increased over the 10-year period at rates of 0.60 ppm yr À1 . The increase in amplitude has been attributed to increasing assimilation and release of CO 2 by terrestrial ecosystem and the advance of spring drawdown to climate warming (Keeling et al, 1996;Piao et al, 2008), suggested that terrestrial ecosystems in Northern Hemisphere were experiencing greater CO 2 uptake during the growing season and greater CO 2 release during period outside the growing season (Sitch et al, 2015).…”
Section: Seasonal Variations Of Co 2 Concentration Over Terrestrial Ementioning
confidence: 99%
“…It was estimated, by fitting a harmonic model to monthly-mean ACTE, seasonal amplitude of ACTE increased over the 10-year period at rates of 0.60 ppm yr À1 . The increase in amplitude has been attributed to increasing assimilation and release of CO 2 by terrestrial ecosystem and the advance of spring drawdown to climate warming (Keeling et al, 1996;Piao et al, 2008), suggested that terrestrial ecosystems in Northern Hemisphere were experiencing greater CO 2 uptake during the growing season and greater CO 2 release during period outside the growing season (Sitch et al, 2015).…”
Section: Seasonal Variations Of Co 2 Concentration Over Terrestrial Ementioning
confidence: 99%
“…The use of MeMo as a predictive tool to estimate the past and future global CH 4 soil sink relies strongly on the use of soil moisture from standard climate models, such as output from land surface models or dynamic global vegetation models (DGVMs). Therefore, gaps in the Dorigo et al (2011) data set were filled using soil moisture data from an ensemble of nine DGVMs (TRENDY; Sitch et al, 2015). The R99 model parameterizes the effect of soil moisture on CH 4 uptake fluxes as a function of precipitation and evaporation, and therefore R99 was forced using monthly data sets of precipitation (CRU3.1; Harris et al, 2014) and evapotranspiration (TRENDY; Sitch et al, 2015).…”
Section: Forcing Datamentioning
confidence: 99%
“…Therefore, gaps in the Dorigo et al (2011) data set were filled using soil moisture data from an ensemble of nine DGVMs (TRENDY; Sitch et al, 2015). The R99 model parameterizes the effect of soil moisture on CH 4 uptake fluxes as a function of precipitation and evaporation, and therefore R99 was forced using monthly data sets of precipitation (CRU3.1; Harris et al, 2014) and evapotranspiration (TRENDY; Sitch et al, 2015). Temperature forcing is constrained by global data sets for surface temperature as a proxy for soil temperature (CRU3.1; Harris et al, 2014).…”
Section: Forcing Datamentioning
confidence: 99%
“…The reduced ability of the land surface to absorb increased anthropogenic CO 2 emissions in the future has been shown by models and inferred from observations (Friedlingstein et al, 2006;Canadell et al, 2007; Published by Copernicus Publications on behalf of the European Geosciences Union. 2652 D. Slevin et al: Global evaluation of gross primary productivity in the JULES land surface model v3.4.1 Friedlingstein et al, 2014;Sitch et al, 2015). Friedlingstein et al (2006) and Friedlingstein et al (2014) have suggested that a major source of model uncertainty is the land C cycle which can affect the ability of Earth system models (ESMs; also known as coupled carbon-cycle-climate models) to reliably simulate future atmospheric CO 2 concentrations and climate (Dalmonech et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The Joint UK Land Environment Simulator (JULES) has been evaluated on various scales: point Slevin et al, 2015;Ménard et al, 2015), regional (Galbraith et al, 2010;Burke et al, 2013;Chadburn et al, 2015) and globally as part of model-intercomparison studies (Anav et al, 2015;Sitch et al, 2015). Evaluating simulated GPP on a range of scales and its sensitivity to spatial resolution and meteorological data is essential for informing future model developments.…”
Section: Introductionmentioning
confidence: 99%